2023
DOI: 10.1186/s12933-023-02028-7
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride-glucose index predicts 1-year major adverse cardiovascular events in end-stage renal disease patients with coronary artery disease

Enmin Xie,
Zixiang Ye,
Yaxin Wu
et al.

Abstract: Background The triglyceride-glucose (TyG) index has been suggested as a dependable indicator for predicting major adverse cardiovascular events (MACE) in individuals with cardiovascular conditions. Nevertheless, there is insufficient data on the predictive significance of the TyG index in end-stage renal disease (ESRD) patients with coronary artery disease (CAD). Methods This study, conducted at multiple centers in China, included 959 patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Recently, METS-IR and TyG-BMI have been recognized as a more reliable indicators for assessing IR [ 33 , 37 ]. In our study, METS-IR and TyG-BMI index had a larger AUC area for AF recurrence after ablation, compared to traditional risk factor BMI and AF type, although LA diameter had a larger AUC area than METS-IR and TyG-BMI index.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, METS-IR and TyG-BMI have been recognized as a more reliable indicators for assessing IR [ 33 , 37 ]. In our study, METS-IR and TyG-BMI index had a larger AUC area for AF recurrence after ablation, compared to traditional risk factor BMI and AF type, although LA diameter had a larger AUC area than METS-IR and TyG-BMI index.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al included 959 patients with CAD and end-stage renal disease, showed that The probability of MACE is the highest in patients with TyG index >9.4 mmol/L, compared to the lowest group of TyG index ≤8.77 mmol/L . Adding TyG index to the traditional model have promoted the predictive value of forecasting MACE [24]. And for patients with severe ischemic stroke, TyG index and in-hospital mortality were positively correlated [25].…”
Section: Discussionmentioning
confidence: 99%
“…Among CVD patients, an elevated TyG index has been associated with an increased risk of major adverse cardiovascular and cerebrovascular events in individuals with stable CHD combined with T2DM [ 16 ]. Numerous studies have independently confirmed the association of the TyG index with MACEs in patients with ACS, irrespective of T2DM status [ 17 23 ]. In our study, we also noted that an elevated TyG index beyond 8.77 and 8.62 was significantly associated with increased risks of both all-cause mortality and MACEs.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, numerous studies have been conducted to ascertain if the TyG index can act as an alternative indicator of IR in stratifying the risk for adverse outcomes. The TyG index is not only associated with the occurrence of cardiovascular disease (CVD) [7][8][9][10][11][12][13][14][15] but also with adverse outcomes in patients with CVD [16][17][18][19][20][21][22][23]. Numerous studies have independently confirmed the association of the TyG index with adverse outcomes in CHD patients, both with and without T2DM [18,24,25].…”
Section: Introductionmentioning
confidence: 99%